[Lighthouse] - (:unkn) unknown (My University, 2010)
Photograph of the Port of Spain lighthouse with Customs Office and a small section of the St. Vincent Jetty. Many people have congregated in the street and there are rows of policemen standing near the lighthouse. It appears a parade or procession is about to start. In the foreground are two wooden, canvas-topped launch boats and in the background are the roofs of buildings and the Northern Range.
Colour: Black and White; Style: Portrait; Other: Bordered; Divided
Keywords: Trinidad and Tobago; Postcards; Lighthouses--Trinidad and Tobago; Docks--Trinidad and Tobago; Mountains--Trinidad and Tobago; Boats and boating--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Harbors--Trinidad and Tobago; Jetties--Trinidad and Tobago; Ports of entry--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Uniforms--Trinidad and Tobago; Police--Uniforms